DNA interstrand cross-links induced by the major oxidative adenine lesion 7,8-dihydro-8-oxoadenine - Aaron L. Rozelle (Nature Portfolio, 2021)
7,8-dihydro-8-oxoguanine and 7,8-dihydro-8-oxoadenine (oxoA) are generated upon oxidative damage to DNA, but the biological effects of oxoA are not well known. Here, the authors report that only oxoA forms DNA interstrand crosslinks (ICLs) upon secondary oxidation and that these ICLs can be induced by reactive halogen species, one-electron oxidants and the myeloperoxidase/H2O2/Cl- system.